Monitoring the Neurotransmitter Response to Glycemic Changes Using an Advanced Magnetic Resonance Spectroscopy Protocol at 7T - Park, Young Woo; Deelchand, Dinesh K.; Joers, James M.; Kumar, Anjali; Alvear, Alison Bunio; Moheet, Amir; Seaquist, Elizabeth R.; Öz, Gülin (Frontiers in Neurology, 2021)
The primary excitatory and inhibitory neurotransmitters glutamate (Glu) and gamma-aminobutyric acid (GABA) are thought to be involved in the response of the brain to changes in glycemia. Therefore their reliable measurement is critical for understanding the dynamics of these responses. The concentrations of Glu and GABA, as well as glucose (Glc) in brain tissue can be measured in-vivo using proton (1H) magnetic resonance spectroscopy (MRS). Ultrahigh field MR scanner technology combined with advanced MRS methodology allows reliable monitoring of the concentrations of these metabolites in different brain regions under changing metabolic states. However, the long acquisition times (over 1-hour) needed for these experiments while maintaining blood glucose levels at predetermined targets in the scanner present many challenges such as subject motion. Here we present an advanced MRS acquisition protocol that combines commercial 7T hardware (7T Siemens Scanner and Nova Medical head coil), BaTiO3 dielectric padding, optical motion tracking, and dynamic frequency and B0 shim updates to ensure the acquisition of reproducibly high-quality data. Data were acquired with a semi-LASER sequence (TR/TE = 5000/26ms) from volumes-of-interests (VOIs) in the prefrontal cortex (PFC) and hypothalamus (HTL). Five healthy volunteers were scanned to evaluate the effect of the BaTiO3 pads on RF transmit energy (B1+) distribution. The use of BaTiO3 padding in the Nova coil resulted in a 60% gain in signal-to-noise ratio in the PFC VOI over the acquisition without the pad. The protocol was then tested in six patients with type 1 diabetes during a clamp study where euglycemic (~100mg/dL) and hypoglycemic (~50mg/dL) blood glucose levels were maintained in the scanner. The new protocol allowed retention of all HTL data compared to our prior experience of having to exclude ~half of the HTL data in similar glucose clamp experiments in the 7T scanner due to subject motion. The advanced MRS protocol showed excellent data quality (reliable quantification of 12 and 11 metabolites for PFC and HTL, respectively) and stability (p > 0.05 for both signal-to-noise ratio and water linewidths) between euglycemia and hypoglycemia. This protocol will allow robust mechanistic investigations of the primary neurotransmitters, Glu and GABA, under changing glycemic conditions.